Whole genome sequencing demonstrates substantial pathophysiological differences of MYC rearrangements in patients with plasma cell myeloma and B-cell lymphoma. Issue 14 (6th December 2021) - Bendig, Sonja; Walter, Wencke; Meggendorfer, Manja; Bär, Constance; Fuhrmann, Irene; Kern, Wolfgang; Haferlach, Torsten; Haferlach, Claudia; Stengel, Anna
Abstract: MYC rearrangements ( MYC r) occur in several B-cell neoplasms and impact disease progression and overall survival. We used whole genome sequencing (WGS) and whole transcriptome sequencing (WTS) to analyze and compare MYC r in different B-cell neoplasms. The MYC r features of cases with plasma cell myeloma (PCM) ( n = 88) showed distinct characteristics compared to cases with mature B-cell lymphomas ( n = 62, including Burkitt lymphoma (BL), diffuse large B-cell lymphoma (DLBCL) and high grade lymphoma with MYC and BCL2 and/or BCL6 rearrangements (HGBL)): they were more complex and showed a wider variety of translocation partners and breakpoints. Additionally, unlike B-cell lymphomas, they showed no evidence of activation-induced deaminase (AID) involvement in the formation of MYC r with immunoglobolin heavy chain (IGH), indicating a different mechanism of origin. The different MYC r characteristics resulted in poor MYC r detection rates by fluorescence in situ hybridization of only 50% in PCM, compared to 94% in lymphoma.